Innovation of online-based periodic salary increase services in the Bandung city personnel and human resources development agency - Widiati, Eviana; Dinata, Ihsan Ratma; Susangka, Tatang Hardi; Fauziah, Riska; Hasanah, Vina Febriyanti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Public service is the government's responsibility to its citizens as mandated by the 1945 Constitution. The Bandung City Personnel and Human Resources Development Agency is a government agency that provides public services. To improve services, the Bandung City Personnel and Human Resources Development Agency has made innovations in the Personnel Information System. This Personnel Information System Program includes several integrated features. The author chooses to focus on the online-based periodic salary increase service features. The purpose of this study is to determine whether this online-based periodic salary increase service innovation meets the characteristics of successful innovation. Using the theory of Everett M. Rogers which has five factors, namely relative advantage, compatibility, complexity, trialability, and observability. The research method used is descriptive qualitative research by collecting the required data, both primary and secondary data from interviews, observations, documentation, and literature studies. The results of the study indicate that the online-based periodic salary increase service innovation at the Bandung City Personnel and Human Resources Development Agency can be stated to have fulfilled the service innovation factors, making it more effective and efficient.